A low incidence of iodine‐induced hyperthyroidism following administration of iodinated contrast in an iodine‐deficient region. (19th June 2015) - Jarvis, Carol; Simcox, Kim; Tamatea, Jade A. U.; McAnulty, Kim; Meyer‐Rochow, Goswin Y.; Conaglen, John V.; Elston, Marianne S.
Summary: Objective: There are limited data on the incidence of iodinated contrast‐induced thyrotoxicosis, particularly in iodine‐deficient regions. The aim of this study was to determine the incidence of iodinated contrast‐induced thyrotoxicosis and to determine whether thyrotoxicosis was more common in patients ≥70 years compared to those <70 years of age. Design: A prospective study of adult patients undergoing an outpatient CT with iodinated contrast was performed. Measurements: Thyroid function tests (TFTs) and urine iodine measurements were performed prior to the scan. TFTs were repeated at 4‐ and 8‐weeks postscan. Changes in TFTs from baseline were analysed. Results: A total of 102 patients were included in the final analysis. Overall, TSH levels dropped ( P  = 0·0002), and free T3 (FT3 ) levels increased ( P  = 0·04) between baseline and week 4 with normalization by week 8; however, these changes were not considered clinically significant. No significant differences in free T4 (FT4 ) occurred in the overall group ( P  = 0·82). There were no differences in TFTs between baseline and 4 or 8 weeks for those patients aged <70 compared to ≥70 years. Two patients developed new subnormal TSH values. Of these, one had a 90‐mm follicular variant papillary thyroid carcinoma diagnosed while the other had a normal thyroid assessment and TSH spontaneously normalized by 12 weeks. Conclusions: Only 2% of patients developed subclinical hyperthyroidism following a standard dose of iodinated contrast for CT investigations. Given the low incidence of iodine‐induced thyrotoxicosis, there is no indication for routine pre‐ and post‐CT thyroid function testing in our region.